2014
DOI: 10.1002/2013wr015070
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between neighboring vegetation patches: Impact on flow and deposition

Abstract: Flow and sedimentation around patches of vegetation are important to landscape evolution, and a better understanding of these processes would facilitate more effective river restoration and wetlands engineering. In wetlands and channels, patches of vegetation are rarely isolated and neighboring patches influence one another during their development. In this experimental study, an adjacent pair of emergent vegetation patches were modeled by circular arrays of cylinders with their centers aligned in a direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 47 publications
(111 reference statements)
3
93
1
Order By: Relevance
“…This vegetation driven spatial heterogeneity (VDSH) stems from differential soil development and evolution processes between areas under canopies and bare ground (e.g., Bhark and Small (2003), Caldwell, Young, McDonald, andZhu (2012), De Ploey (1984), and Nulsen, Bligh, Baxter, Solin, and Imrie (1986)) resulting in feedback mechanisms perpetuating or further accentuating the bare groundunder canopy soil dichotomy (Puigdefabregas et al, 1999). In addition, observations in semiarid rangelands suggest that deposition mounds form upstream of plant clumps as a result of energy losses and changes in transport capacity that accompany overland flow diversion by plant stems (e.g., Meire, Kondziolka, and Nepf (2014) and Rominger and Nepf (2011)). The entrapment of nutrients along with sediments in these mounds creates areas of nutrients concentration where plants thrive spatially alternated by bare or poorly vegetated zones of water and nutrient depletion, forming the premise of the "resource islands" or "vegetation island" concept (e.g., Li, Zhao, Zhu, Li, and Wang (2007) and Ridolfi, Laio, and D'Odorico (2008)).…”
Section: Effects Of Vegetation Community Structure On Concentrated Flmentioning
confidence: 99%
“…This vegetation driven spatial heterogeneity (VDSH) stems from differential soil development and evolution processes between areas under canopies and bare ground (e.g., Bhark and Small (2003), Caldwell, Young, McDonald, andZhu (2012), De Ploey (1984), and Nulsen, Bligh, Baxter, Solin, and Imrie (1986)) resulting in feedback mechanisms perpetuating or further accentuating the bare groundunder canopy soil dichotomy (Puigdefabregas et al, 1999). In addition, observations in semiarid rangelands suggest that deposition mounds form upstream of plant clumps as a result of energy losses and changes in transport capacity that accompany overland flow diversion by plant stems (e.g., Meire, Kondziolka, and Nepf (2014) and Rominger and Nepf (2011)). The entrapment of nutrients along with sediments in these mounds creates areas of nutrients concentration where plants thrive spatially alternated by bare or poorly vegetated zones of water and nutrient depletion, forming the premise of the "resource islands" or "vegetation island" concept (e.g., Li, Zhao, Zhu, Li, and Wang (2007) and Ridolfi, Laio, and D'Odorico (2008)).…”
Section: Effects Of Vegetation Community Structure On Concentrated Flmentioning
confidence: 99%
“…Based on analysis of the experimental results, a scour pool developed when the flow blockage 2aWv/W was approximately >5.0 because the flow accelerated through the contraction. A local scour pool did not develop when the ratio of the obstruction width to the channel width 2Wv/W was <0.4 because the flow induced by the obstructions was independent [16]. We found that the scoured region induced by acceleration of the flow moved further downstream as the flow blockage decreased.…”
Section: Changes In Bed Topographymentioning
confidence: 70%
“…When the flow blockage increases, the diverging flow from the porous obstructions increases due to higher drag, leading to greater magnitude of the velocity and turbulence at the center of the channel. In particular, the flow between paired obstructions is similar to a turbulent jet at higher flow blockage [16].…”
Section: Scour Poolmentioning
confidence: 95%
“…It can be assumed that vegetation defines the flow conditions in the channel during periods of high discharge. Flow conditions at various plant configurations were also investigated among others by [6][7][8][9][10]. Yang et al [11] studied the hydraulic characteristics of overland flow.…”
Section: Introductionmentioning
confidence: 99%